PHYSICAL THERAPIST EVALUATION IN FITNESS CENTER: ANALYSIS OF MOST COMMON INJURED CORPORAL SEGMENT. (Fiep Bulletin - online, 2013)
It is increasingly evident the importance of physical exercises in people's lives for the maintenance of a good health and as prevention of illnesses. If carried out regularly, they stimulate the promotion of quality of life and present an inverse relation regarding the risk of chronic-degenerative illnesses. Even so, some people still present certain resistance or do not accept such recommendations regarding this practice. Individuals with injuries or restrictions in the musculoskeletal system stimulate professionals of the health area to create adaptations for physical exercises in fitness centers. The aim of this study is to analyze the most common injured corporal segments in a fitness center through records of physical therapist evaluation and its relations to the gender and age. It was carried out through the analysis of 102 records, since the knee joint and the lumbar spine, in a general way, had been the most damaged corporal segments, and the most expressive age group was shown to be among individuals from 21 to 30 years old. One expects that, with this study, the operating professionals of health area in fitness center give greater emphasis to the procedures of evaluation of individuals that intend to initiate physical exercises programs, and that present injuries or restrictions in the musculoskeletal system.
Keywords: physical therapist evaluation; fitness center; injuries.